Inception - Nolan, Christopher; DiCaprio, Leonardo; Watanabe, Ken; Warner Bros. Picture (Burbank, California : Warner Bros. Pictures, 2010)
Dom Cobb is the best there is at extraction; stealing valuable secrets inside the subconscious during the mind's vulnerable dream state. His skill has made him a coveted player in industrial espionage, but also has made him a fugitive and cost him dearly. Now he may get a second chance if he can do the impossible; inception, planting an idea rather than stealing one. If they succeed, Cobb and his team could pull off the perfect crime.
Special features: Dreams: cinema of the subconscious - Can dream world be a fully functional parallel reality? Joseph Gordon-Levitt and leading scientists take you to the cutting edge of dream research ; Inception: the Cobol job-comic prologue in full animation and motion: see the events that led to the beginning of the movie ; 5.1 soundtrack selections from hans Zimmer's versatile score.
Executive producers, Chris Brigham & Thomas Tull ; director of photography, Wally Pfister ; music, Hans Zimmer.
Leornardo DiCaprio, Ken Watanabe, Joseph Gordon-Levitt, Marion Cotillard, Ellen Page, Tom Hardy, Cillian Murphy, Tom Berenger and Michael Caine.
LPF: PG13
DVD format, Widescreen (16:9), Region 3, Dolby Digital, Dual-layer format.
In English and Thai with optional English, Thai, Korean, Cantonese, Bahasa Indonesia & Chinese.
Keywords: Business intelligent -- Drama; Crime films